Quantitative proteomic analysis reveals the effects of mu opioid agonists on HT22 cells - Zhang, Xutong; Lou, Yani; Zheng, Dongxu; Lu, Jialin; Qi, Dansi (Frontiers in Pharmacology, 2023)
At present, the mu opioid receptor is the most important neuroaesthetics receptor in anesthesiology research, and the damage that it does to the nervous system is unknown. We investigated the effects of loperamide, an agonist of the mu opioid receptor, on protein expression in HT22 cells using stable isotope labeling of amino acids in cell culture (SILAC), immobilized metal affinity chromatography (IMAC) enrichment, and high-resolution liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 7,823 proteins were identified. Bioinformatic analysis revealed that mu opioid receptor agonism can induce distinct changes in the proteome of HT22 cells. These findings improve our understanding of narcotic drugs.